Prognostic factors after treatment for iterative thymoma recurrences: A multicentric experience. (December 2019) - Chiappetta, Marco; Zanfrini, Edoardo; Giraldi, Luca; Mastromarino, Maria Giovanna; Petracca-Ciavarella, Leonardo; Nachira, Dania; Congedo, Maria Teresa; Aprile, Vittorio; Ambrogi, Marcello Carlo; Lucchi, Marco; Filosso, Pier Luigi; Ruffini, Enrico; et al.
Highlights: Patients underwent surgery presented a remarkable long term survival. MG seems to be a favourable prognostic factor in these patients. Iterative surgery shows a better survival outcome compared to chemo/radiotherapy. Surgery for iterative recurrences may be considered if technically feasible. Abstract: Objectives: Thymomas are rare neoplasms with a low recurrence rate, which are preferably surgically treated. Iterative thymoma surgery has not been well investigated yet. Study aim is to analyse prognostic factors after iterative recurrence treatment. Methods: Clinical, pathological and surgical findings of 155 patients, treated for thymoma recurrence in three high-volume centres from 01/01/1990 to 1/07/2017, were retrospectively reviewed. Recurrence patterns/treatment types (surgery or chemotherapy, radiotherapy or combined) were correlated to overall (OS) and disease free survival (DFS). Results: Myasthenia Gravis was present in 135 (87%) patients. Surgery was performed in 135/155 (87%) patients with 109 (80.7%) complete resections. Sixty (55%)patients experienced a second recurrence surgically treated in 31/60 (52%) cases with 18 (58%) complete resections. Eleven (61%) patients experienced a third recurrence and nine underwent complete resection. Myastenia Gravis (HR: 0.45; 95% CI: 0.20-0.98, p = 0.046), DFS after the initial thymectomy >36 months (HR: 0.9; 95% CI: 0.96-0.99, p = 0.006) and complete second recurrence resection (HR: 1.45; 95% CI 2.07–10.01, p = 0.010) resulted as independent favorable prognostic survival factor. Despite patient selection bias, rewarding long-term survivals was predictable after iterative thymoma surgery (5 and 10 years survival of 79.6% and 64.6%) while a poor prognosis was observed after CT/RT (5 and 10 years OS of 56.7% and 21.5%), Masaoka stage and DFS > 36 months were risk factor for iterative recurrences. Conclusions: Myasthenia Gravis and long DFS after thymectomy are favorable survival factors for multiple thymoma recurrences. Iterative surgical treatment is a viable therapeutic option associated to long-term survival if technically and clinically feasible.